Analysis of venom sac constituents from the solitary, aculeate wasp Cerceris rybyensis. (November 2019) - Kote, Sachin; Faktor, Jakub; Dapic, Irena; Mayordomo, Marcos Yebenes; Kocikowski, Mikołaj; Kagansky, Alexander; Goodlett, David; Vojtesek, Borivoj; Hupp, Ted; Wilcockson, David; Piper, Ross
Abstract: Solitary aculeate wasps are abundant and diverse hymenopteran insects that disable prey using venom. The venom may possess neuromodulation, immunomodulatory, metabolic-modulatory and antimicrobial functions. Venom analysis of transcriptomes and proteomes has been previously performed in social and parasitoid wasp species. We develop methodologies including mass spectrometry-based shotgun proteomics to analyse the protein constituents from venom sacs of the solitary aculeate wasp Cerceris rybyensis. The venom sac constituents of C. rybyensis are discussed with respect to other wasp species. Highlights: Demonstrating the capacity to characterise protein elements of venom from single venom sacs of small specimens. Venom sac protein inventory from the wasp Cerceris rybyensis, which exhibits intriguing behavioural ecology. Identification of unusual venom sac components in C. rybyensis.